TRADITIONS AND NOVATION IN THE CULTURAL IMAGE OF THE NORTH CAUCASUS IN THE SECOND HALF OF THE XIX CETURY - Abdulhalim Goybaskhanov (Гуманитарные и юридические исследования)
The article describes the dialogue between the North-Caucasus tradition and cultural novation, penetrating the everyday life of local highlanders after joining the Russian Empire. The status and prestige of the suggested renovation artefacts played a big role in this process. The role of educational and cultural organization, which were introduced in the region by the Russian side, in the development of the common understanding and making up the peaceful and creative lift in the north-eastern part of the Caucasus is underlined. The activities of imperial intellectuals were of great importance as they contributed to the appearance of highland educators, connected local cultural traditions and cultural innovations. Their activities promoted the introduction of imperial cultural stereotypes into highland surroundings, showed perspectives for the local development.